Disabled Women's Rights in Indonesian Islamic Family Law: A Mubadalah Perspective - Adelheid El Masrar; Ahmad Burhanuddin; M. Anwar Nawawi (Journal of Islamic Mubadalah, 2024)
This article examines gender discrimination against women with disabilities, this discrimination is due to the article on polygamy regulated in Islamic family law. The question to be answered is how are the rights of women with disabilities in Islamic family law in the perspective of mubadalah? Then what are the steps to fulfill the rights of women with disabilities in Islamic family law? The method of this article uses qualitative, the type of research article is library research, namely literature study, the approach is carried out normatively, which is focused on the Polygamy Article in Islamic Family law, the theory used is mubadalah. The results show that Islamic family law governing polygamy shows a gender-biased law that discourages women with disabilities. The article on polygamy is not in line with the values of equality in mubadalah theory. Recommendations, the polygamy article needs a judicial review to the Constitutional Court, changing the article to make it more equal between men and women.